2018
DOI: 10.1093/jn/nxy197
|View full text |Cite
|
Sign up to set email alerts
|

'Changes in Kidney Function Do Not Differ between Healthy Adults Consuming Higher- Compared with Lower- or Normal-Protein Diets: A Systematic Review and Meta-Analysis

Abstract: BackgroundHigher-protein (HP) diets are advocated for several reasons, including mitigation of sarcopenia, but their effects on kidney function are unclear.ObjectiveThis meta-analysis was conducted to determine the effect of HP intakes on kidney function in healthy adults.MethodsWe conducted a systematic review and meta-analysis of trials comparing HP (≥1.5 g/kg body weight or ≥20% energy intake or ≥100 g protein/d) with normal- or lower-protein (NLP; ≥5% less energy intake from protein/d compared with HP grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 75 publications
4
42
1
Order By: Relevance
“…During OLE, no (further) change in eGFR was observed in any of the (sub)groups. The alteration of eGFR in response to a high protein diet is in line with observations by others and is thought to be an adaptive response to the protein feeding and not the development of CKD per se [31,33,34]. The observed plateau in eGFR after 13 weeks of treatment with 2 servings of WP-MND during the OLE period, supports this notion of adaptation.…”
Section: Protein Intake and Kidney Functionsupporting
confidence: 89%
See 1 more Smart Citation
“…During OLE, no (further) change in eGFR was observed in any of the (sub)groups. The alteration of eGFR in response to a high protein diet is in line with observations by others and is thought to be an adaptive response to the protein feeding and not the development of CKD per se [31,33,34]. The observed plateau in eGFR after 13 weeks of treatment with 2 servings of WP-MND during the OLE period, supports this notion of adaptation.…”
Section: Protein Intake and Kidney Functionsupporting
confidence: 89%
“…The consistent high protein intake in line with recommendations, especially in participants receiving 2 servings of WP-MND throughout the entire 26-week study period (during RCT and OLE), enabled evaluation of the effect of a prolonged high protein intake on kidney function. Concerns regarding the adverse effect of a high protein diet on kidney function are related to glomerular hyperfiltration and hypertensive effects [31][32][33]. During the RCT, eGFR increased in the test vs. no change in the control group (p = 0.002).…”
Section: Protein Intake and Kidney Functionmentioning
confidence: 99%
“…Whether restricted protein intake is necessary for the patient with DN is still under debate; [ 7–9 ] soy proteins substitution has been shown to improve renal function in patients with DN. [ 16 ] Clinical trials indicated that ingestion of a soy protein decreases urinary urea nitrogen concentrations, proteinuria, blood sodium levels, and serum and urinary creatinine levels in patients with DN.…”
Section: Discussionmentioning
confidence: 99%
“…Available data debates the idea that restricted protein intake is necessary for the patient with DN. [ 7–9 ] Previous studies have that soy‐based dietary protein protects renal function in DN related to type 1 diabetes. [ 10,11 ] In the streptozotocin (STZ)‐induced diabetic rat model, soy proteins helped to maintain aquaporin and osteoponitn expression, [ 12 ] and genistein repressed renal inflammation and fibrosis that is associated with tyrosine kinase inhibition in mesangial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these per meal protein intakes, it has been suggested that the current recommended dietary allowance (RDA) for protein of 0.8 g·kg −1 ·day −1 is suboptimal for the maintenance of skeletal muscle mass with advancing age. However, increasing protein intakes up to 1.2-2.0 g·kg −1 ·day −1 has been shown to reduce long-term lean mass loss in the elderly [13], and has been shown to have no negative side-effects on health outcomes such as kidney function [14]. Oftentimes the overnight period is overlooked as a window of opportunity to increase protein intake.…”
mentioning
confidence: 99%